Alinhavos de tinta: o ato de tatuar-se na narrativa de sofrimento de um jovem adulto - Macedo, Sybele (2020)
Psychoanalysis, since its beginnings, has been concerned with issues related to the body. More recently, the proliferation of aesthetic intervention practices such as plastic surgery, piercings and tattoos have been attracting the attention of psychoanalysts and researchers who, in some way, allow themselves to be affected by psychoanalysis. The study, observation and clinical practice led the author to establish the act of getting oneself tattooed as a central object of investigation. Increasingly widespread in contemporary times, tattooing is no longer restricted to ghettos of exclusion, as it was two or three decades ago. It is common to find tattooed bodies in different contexts and in individuals of different ages or social classes. As a result, interest in the practice spread to different fields of knowledge. The practice of piercing the body by inserting new elements into the skin - the pigments - has subjective implications that refer to a form of language, being able to work in the service of an identity search or as a memory resource. Tattoos are often described as a second skin or as walls to protect oneself. There is also something in this practice that seems to be related to compulsion to repetition and jouissance. The act of getting oneself tattooed was, in this work, taken in a singular way, distancing itself from an analysis based only on the images, symbols and letters engraved on the skin. To the same extent, it was analyzed from the construction of the case of the young adult participating in the research. The established hypothesis was that the act of getting oneself tattooed can operate as a subjective way out of the research participant's psychological distress, coming to allay his anguish at times when it becomes overwhelming. This hypothesis was contemplated from the analysis of the corpus, which consisted of the reports of the meetings between the participant and the researcher. The general objective was to investigate the function of the act of tattooing in the narrative of psychological suffering of the young adult participating in the research, in order to enable discussions about the particularity of this mode of body intervention, starting from the singularity of a case study, analyzed under the light of Freud and Lacan's psychoanalysis. Psychoanalysis, through the construction and analysis of a clinical case, was chosen as a theoretical and methodological support for INK BASTING: THE ACT OF GETTING ONESELF TATTOOED IN THE SUFFERING NARRATIVE OF A YOUNG ADULT 11 conducting this research, so that it made possible the expression of the singularity of the being who suffers - the research participant - and of the speech addressed to the researcher. Through the case, it was also expected to promote a diagnosis, articulating malaise, suffering and symptom to the act of tattooing on the research participant's narrative of suffering. The apprehension of a case is always unique, but from its construction and analysis, it may be possible to infer something particular about the contemporary tattoo phenomenon. Therefore, it is expected to be possible to expand the discussions about its social impact and its place in the psychoanalytic clinic. In addition, psychoanalytic research and its circulation and discussion in academia can contribute to the incidence of psychoanalysis in the contemporary social bond, thus constituting a political bet. A case may also cause psychoanalysis to move towards understanding what it says in a different way.